Cassava starch in the Brazilian food industry - Demiate, Ivo Mottin; Kotovicz, Valesca (My University, 2011)
Cassava starch is a valued raw material for producing many kinds of modified starches for food applications. Its physicochemical properties, as well as its availability, have made it an interesting and challenging ingredient for the food industry. In the present work, food grade modified cassava starches were purchased from producers and analyzed for selected physicochemical characteristics. Samples of sour cassava starch were included, as well as one sample of native cassava starch. Results showed that almost all modified starches were resistant to syneresis, produced pastes more stable to stirred cooking, and some of them were difficult to cook. The sour cassava starches presented high acidity and resulted in clear and unstable pastes during stirred cooking, susceptible to syneresis.

O amido de mandioca é uma matéria-prima valorizada para a produção de diversos tipos de amidos modificados para serem utilizados pela indústria de alimentos. As propriedades físico-químicas e sua disponibilidade o colocam como um ingrediente interessante e desafiador para a indústria alimentícia. Neste trabalho, amidos de mandioca modificados de uso alimentício foram adquiridos ou recebidos de produtores e analisados em relação a algumas características físico-químicas. Amostras de polvilho azedo e uma de amido nativo de mandioca foram incluídas no estudo. Os resultados mostraram que quase todos os amidos modificados foram resistentes à sinérese, produziram pastas mais estáveis ao cozimento sob agitação e algumas eram de difícil cozimento. Os polvilhos azedos apresentaram elevados valores de acidez e produziram pastas claras e instáveis ao cozimento que também foram susceptíveis à sinérese.
Amido de mandioca na indústria brasileira de alimentos
Keywords: Modified starches; Sour cassava starch; Manihot esculenta; Thickener; Gelatinization